Diseño de un cuadro de mando integral en la gestión administrativa en la fábrica de lacteos leito s. a. ubicada en la provincia de Cotopaxi, cantón Salcedo, vía a Salache panamericana norte durante el año 2013 - Llumiquinga Mendoza, Jesica (2015)
The present research which was developed is aimed to the design of a Balanced Scorecard (BSC), which is considered significant for the factory. The (BCS) is considered as a control tool used to achieve the continuous improvement in each of the areas of the organization and reform the institutional management, integrating measures of monitor and control through of four basic perspectives such as: financial, customers, internal processes, learning and growing. This method translates the strategy into a coherent set of indicators to achieve the institutional vision. First it described in depth the conceptual and theoretical foundations which are the basis of the research, as background to the inquiry it has the Company, Administrative Management, Value Chain, Strategic Planning, Balanced Scorecard and management indicators. Then, a research was done applying interviews to the managers involved in the different areas of the company whose information was very important for the development of the proposal. At the stage….